2018
DOI: 10.7554/elife.32035
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-based herd immunity can limit phage epidemics in bacterial populations

Abstract: Herd immunity, a process in which resistant individuals limit the spread of a pathogen among susceptible hosts has been extensively studied in eukaryotes. Even though bacteria have evolved multiple immune systems against their phage pathogens, herd immunity in bacteria remains unexplored. Here we experimentally demonstrate that herd immunity arises during phage epidemics in structured and unstructured Escherichia coli populations consisting of differing frequencies of susceptible and resistant cells harboring … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 75 publications
3
34
0
Order By: Relevance
“…In contrast, Payne et al . (55) demonstrated that cross-protection against phage T7 can occur between two strains of E. coli , where one harbored a CRISPR-based resistance. Cross-protection was observed both in liquid and on a bacterial lawn.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Payne et al . (55) demonstrated that cross-protection against phage T7 can occur between two strains of E. coli , where one harbored a CRISPR-based resistance. Cross-protection was observed both in liquid and on a bacterial lawn.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, the spatial structure of immune responses mediated by IFN and other cytokines can be determined by the diffusion of signaling molecules and the effect of these signals in receptor cells [12]. In addition to infection and immunity, diffusion-reaction models have been used for addressing a variety of eco-evolutionary questions such as, for instance, how bacterial CRISPR limits viral spread [13] and how spatial obstacles perturb population expansion fronts and promote random genetic drift [14].…”
Section: Introductionmentioning
confidence: 99%
“…235 5A & B), which parallels the decline in phage population sizes over time in the same 236 treatments (regression of ln pfu ml -1 over dpi: β [95% CI] = -2.58 [-3.23, -1.84], t(2) 114 = -7.64, p = 7.27 x 10 -12 ). These data suggest that susceptible hosts are 238 protected by population-level CRISPR diversity, and that this protection is mediated 239 by a reduced ability of phage to replicate on increasingly dilute susceptible hosts 240 (Payne et al, 2018) (Figure S1). affected by -evolutionary emergence.…”
mentioning
confidence: 96%